The Message of Thessalonians Preparing for the coming King - Stott, John R.W. (Leicester Inter-Varsity Press, 1991)
John Stott believes that the Thessalonian letters offer us a model for Christian ministry, a vision for the local church, and an affirmation of the foundation facts of our faith
Keywords: Bible. -- Thessalonians. Thessalonicenzen (bijbelboeken) Christianity -- Scriptures Bible -- N.T -- Thessalonians - Critical studies